The use of a stent-resin-bonded splint combination to stabilize a free gingival autograft - (:unkn) unknown (MOSBY-YEAR BOOK INC, 1999)
This article describes the use of a resin-bonded retainer in combination with an acrylic resin stent to stabilize a free gingival graft. This retainer also prevents migration of muscle attachment after surgery to deepen a section of the vestibule where the oral mucosa closely approached the gingival margin. The acrylic resin stent is attached to the resin-bonded retainer by means of an integrally cast metal framework. After surgery, the retainer is attached to the occlusal two thirds of the buccal surfaces of maxillary molar teeth by using the acid-etched resin bonding technique. The stent effectively retains the graft, is simple to fit, and does not cause any permanent damage to the enamel. It has none of the disadvantages of conventional removable acrylic resin stents.
Keywords: POSTERIOR TEETH